4-Methylpyridinium 2-carboxy-4,5-dichlorobenzoate monohydrate - Smith, Graham (International Union of Crystallography, 2010)
In the structure of the 1:1 proton-transfer compound of 4-methylpyridine (γ-picoline) with 4,5-dichlorophthalic acid, C(6)H(8)N(+)·C(8)H(3)Cl(2)O(4) (−)·H(2)O, determined at 200 K, the 4,5-dichlorophthalate anions are bridged by the water molecule through O—H⋯O(carboxyl) hydrogen bonds, giving zigzag chains which extend along the c-axis direction. The 4-methylpyridinium cations are linked to the chains through single N—H⋯O(water) hydrogen bonds and occupy the voids within the chains in the one-dimensional structure. The anions have the common ‘planar’ conformation with a short intramolecular O—H⋯O(carboxyl) hydrogen bond.